Omega 3 fatty acid supplementation improves physical performance: a systematic review and meta-analysis of RCTs. (3rd October 2022) - Davis, I; McCullough, D; Banach, M; Mazidi, M
Abstract: Background: Omega 3 polyunsaturated fatty acids (n-3, PUFA) show promise for improving muscle mass, strength and measures of physical performance that may ameliorate sarcopenia. Purpose: To perform an updated meta-analysis of n-3 interventions with detailed subgroup analysis on physical performance/strength and muscle mass, with sub-group analysis on duration, age, BMI, sex, and location, amongst others. Methods: We followed The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) –checklist for systematic reviews and meta-analysis. Literature was searched (ISI, Scopus and PubMed databases up to October 2021) with terms related to n-3 (alpha linolenic acid, docosahexaenoic acid, eicosapentaenoic acid, fish oil etc.) muscle mass, strength and physical performance (using the 30 s Chair Stand Test [30CST] for muscle strength and endurance and the Timed Up an Go Test [TUG] for physical performance; both are useful and simple tools that can be used to assess sarcopenia). Human n-3 randomised controlled trials (RCTs) were included and assessed for methodological quality (Cochrane quality assessment tool). Weighted mean differences (WMDs) with 95% confidence intervals (CIs) and random-effect model analysis, and I-squared (I 2 ) statistic were used to assess outcomes and heterogeneity respectively. Subgroup and sensitivity analysis were performed, and Begg's and Egger's tests evaluated publication bias. Statistical analysis used STATA 11 software and a p-value of <0.05 was considered statistically significant. Results: The primary meta-analyses for functional performance (TUG, 7 RCTs, 8 interventions, n=259) and strength (30CST, 5 RCTs, 6 interventions, n=180), favoured n-3 PUFA (p<0.001). TUG (weighted mean change (WMD): −0.35 s; 95% CI: −0.53, −0.18; I 2 =0.0%) (Figure 1A) and 30CST (WMD: 2.23 repetitions; 95% CI: 1.34, 3.32; I 2 =67.6%) (Figure 1B). Subgroup analysis for TUG was significant for female sex (WMD: 2.92 reps; 95% CI: 2.37, 3.46; I 2 =33.1%), BMI ≥25 kg/m 2 (WMD: −0.36 s; 95% CI: −0.58, −0.17; I 2 =16.9%), and for 30CST by duration ≥16 weeks (WMD: 2.60 reps; 95% CI: 1.37, 3.83; I 2 =0.0%) (all p<0.001). There were no significant effects on muscle mass and handgrip strength, and subgroup analysis showed negligible influence. Publication bias was minimal and sensitivity analysis did not influence findings. Conclusions: We showed novel favourable effects of n-3 PUFA on specific measures of strength and physical performance in some populations but not on measures of muscle mass and other strength tests. The beneficial effects of n-3 on these measures may be due to various mechanisms that regulate muscle quality (rather than quantity). Further studies are needed to elucidate the dose, duration and other influential variables. Funding Acknowledgement: Type of funding sources: None.